Improving Agility Performance Among Athletes by Jami Agility Table (JAT) - Jami, Saeed; Irandoust, Khadijeh (International Journal of Sport Studies for Health, 2022)
Context: A model of agility ladder tool was designed in the current study to increase cognitive-motor performance in athletes with more advantages over conventional agility ladders.Objectives: The aim of this study was to develop agility tool for athletes using Jami agility table (JAT) which has been the latest training model by creating mental challenge and recruiting muscle movement units for agile performance of sports skills.Methods: In this descriptive-analytical study, a systematic review of agility development methods were presented to improve psychomotor performance in athletes and then the JAT agility table model was introduced. Based on the JAT, a special code is designed in order to develop agility both physically and mentally aspects, and athlete is always engaged with new algorithms of movement.Results: One of the exclusive functions of JAT, is to increase contextual interference in the performance of motor skills which increases reaction time (RT) in athletes significantly. Laterality detection and empowering non-dominant hemisphere is one of the applications of the JAT, which ultimately increases the comprehensive development of the central nervous system (CNS).Conclusions: The most important aspect of JAT is based on increasing contextual interference and random learning in learners and athletes. Additionally, neuromuscular coordination is one of JAT functions which would improve agility performance in athletes. JAT mechanism has been designed based on Movement algorithm models. In such a training model, which imposes a better cognitive function on the learner and athlete to create better motor memory, the process of constant algorithms is converted into variable and instantaneous algorithms, resulting in more reliable motor outputs.